(untitled) (Eduscotech, 2023)
The current condition of social studies learning, especially at the elementary school level, shows indications that the learning patterns developed by teachers tend to be teacher-centric so that students only become objects of learning. This learning model tends to depart from the basic assumption that social studies learning is only intended to transfer knowledge or concepts from the head teacher to the students. The research results can be concluded as follows: (1) learning procedures using a learning model with a socio-cultural approach provide optimal freedom for students to improvise during learning so as to create a climate and activityconducive learning; (2) The effectiveness of the learning model with a socio-cultural approach in increasing students’ understanding of social studies material. It appears that students’ understanding of the material being taught shows an increasing graph, and at the model testing stage, the results of the evaluation testWhat was done showed that the average learning evaluation score of students taught using a learning model with a socio-cultural approach was higher than the average score of students taught using a conventional learning model; and (3) there is an increase in socio-cultural literacystudents related to material that is taught in social studies learning using a social-cultural approach and based on PAIKEM.